Genetic Diversity and Clonal Linkages of Clostridium perfringens Type-A Isolates from Animal-Origin Foods and Human Diarrhoeal Cases using ERIC-PCR: Insights from One Health Perspective - Kumar, Ritesh; Anjay,; Bhoomika,; Kaushik, Purushottam; Saha Roy, Seuli (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Clostridium perfringens type A is a notable pathogen transmitted through food that causes gastroenteritis and diarrhoea in humans  and animals. Gaining insight into its genetic variation and spread through the food chain is vital for public health, food safety, and  the management of zoonotic diseases. This study explored the genetic connections among C. perfringens type-A isolates obtained  from meat, fish, dairy products, and human diarrhoeal stool samples using Enterobacterial Repetitive Intergenic Consensus PCR (ERIC PCR), with a focus on the One health perspective. A total of 62 C. perfringens type-A isolates from meat and meat products (n=16), fish  and fish products (n=19), milk and milk products (n=16), and human diarrhoeal stool samples (n=11) were analyzed using ERIC-PCR.  Dendrograms were created using the UPGMA method based on the Dice similarity coefficients to evaluate the genetic diversity and  potential transmission between sources. ERIC-PCR uncovered a complex genetic landscape with both clonally related and highly diverse  strains across food and human isolate categories. Several clusters included isolates from both food products and human stool, indicating  possible zoonotic and foodborne transmission. The discriminatory indices varied from 0.7583 (milk) to 0.8713 (fish), indicating different  levels of genetic diversity among food items. The clustering patterns suggest shared contamination sources, cross-sectoral transmission  routes, and the potential persistence of C. perfringens strains in food production environments, posing a significant risk to public health.  This study provides molecular evidence of the genetic overlap between animal-derived food products and human diarrhoeal isolates  of C. perfringens type-A, underscoring the importance of the One health approach for ensuring food safety. Integrated surveillance,  improved hygiene practices, and stringent control measures across the human-animal-environment interface are crucial for reducing  the risk of foodborne C. perfringens infections.
Keywords: ERIC-PCR; Genetic diversity; Food-borne pathogens; One health; Zoonoses